2013
DOI: 10.1007/s10706-013-9614-x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of the Effects of Temperature on the Mechanical Properties of Sandstone

Abstract: An experimental study has been carried out as part of a wider programme of research in order to examine some of the physico-mechanical properties of the Jiaozuo Sandstone after exposure to extremely high temperatures. The mechanical properties of the rock under examination are discussed before the results of the thermo-mechanical response of the sandstone are presented and analysed. The range of temperature to which the sandstone has been exposed is 20-1,200°C. The physical properties considered include the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 9 publications
(8 reference statements)
7
39
0
Order By: Relevance
“…Both sandstones experienced a significant reduction of YoungÕs modulus when the preheating treatments increased from 400 to 800 ¡C, with an average reduction of about 50 % and 40 % for fine and coarse sandstone, respectively. Similar variation patterns of the YoungÕs modulus of sandstone under increasing temperature were reported by Wu et al (2013). …”
supporting
confidence: 85%
See 2 more Smart Citations
“…Both sandstones experienced a significant reduction of YoungÕs modulus when the preheating treatments increased from 400 to 800 ¡C, with an average reduction of about 50 % and 40 % for fine and coarse sandstone, respectively. Similar variation patterns of the YoungÕs modulus of sandstone under increasing temperature were reported by Wu et al (2013). …”
supporting
confidence: 85%
“…Temperature dependent mechanical parameters such as strength, elastic modulus and Poisson's ratio are the basic parameters relevant to deep underground excavation support design and stability analyses. Hence, the impact of high temperatures on rocks is considered as an important topic in rock mechanics.The deformation mechanisms and failure criteria of different types of rocks at high temperatures has been studied by various researchers (Stesky et al 1974;Heuze 1983;Rao et al 2007;Wan et al 2009;Zhang et al 2009;Chen et al 2012;Ranjith et al 2012;Brot-ns et al 2013;Wu et al 2013;Liu et al 2013;Zhang et al 2014) and it has generally been shown that high temperature has a significant effect on the mechanical properties of rocks. However, the extent of the effect has been shown to vary for different types of rock, depending on factors such as mineral composition, porosity, density, and presence of cracks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental studies have been conducted on different rocks, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] with an objective to observe and explain the behavior of physical and mechanical properties of these rocks under high temperature or after thermal treatment. All these experimental works are focus on sandstone [4][5][6][7], granite [1,[8][9][10], carbonates [2] and gabbro [11].…”
Section: Introductionmentioning
confidence: 99%
“…All these experimental works are focus on sandstone [4][5][6][7], granite [1,[8][9][10], carbonates [2] and gabbro [11]. However, few studies are interested on the gneiss rock microscopic analysis of thin section of the heated specimen.…”
Section: Introductionmentioning
confidence: 99%